An Elevated Influence of the Low‐Latitude Drivers on the East Asian Winter Monsoon After Around 1990 - Bozhou Chen; Keyan Fang; Zepeng Mei; Tinghai Ou; Feifei Zhou; Hao Wu; Zheng Zhao; Deliang Chen (International Journal of Climatology, 2024)
Current East Asian winter monsoon (EAWM) indices effectively depict the associated high‐ and low‐latitude atmospheric circulations. However, the spatial dynamics of the winter coldness within the monsoon domain are not well adequately represented by EAWM indices. We introduce a novel approach to classify winter temperatures based on both their co‐variability and their mean values. We classified the EAWM domain into three distinct modes: northern (ranging from −27°C to −15°C), central (−14°C to 5°C), and southern (6°C to 27°C). The northern mode, characterised by intense coldness, correlates with a strengthened westerlies that traps Arctic cold air masses during the positive phase of the Arctic Oscillation (AO). In contrast, the southern mode is primarily influenced by low‐latitude oceanic and atmospheric patterns, particularly for near‐coast areas. The central mode, representing an interplay of both high and low‐latitude processes, encapsulates the comprehensive characteristics of the EAWM. Our analysis reveals a notable shift in the relationships among the northern, central, and southern modes around 1990. Prior to this year, the EAWM was predominantly influenced by northern atmospheric patterns, while there is a discernible increase in the influence of low‐latitude drivers afterwards. This shift may be linked to the significant warming in the western Pacific and Indian Oceans, underscoring the heightened role of low‐latitude drivers on the EAWM.